1994
DOI: 10.1063/1.870829
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary magnetohydrodynamic plasmas

Abstract: We develop a filamentary construct of magnetohydrodynamical plasma dynamics based on the Elsasser variables. This approach is modeled after discrete vortex models of hydrodynamicai turbulence, which cannot be expected in general to produce results identical to ones based on a Fourier decomposition of the fields. La a highly intermittent plasma, the induction force is small compared to the convective motion, and when this force is neglected, the plasma vortex system is described by a Hamiltonian. For a system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It is becoming more apparent that microscopic filamentary structures [1][2][3][4] are a fundamental feature of magnetized plasmas that are far from thermal equilibrium. Magnetic field-aligned filamentary structures can consist of density depletions or enhancements, localized pressure changes, current channels, charged flux tubes, or combinations thereof, depending upon the specific boundary conditions and sources that drive the plasma away from thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming more apparent that microscopic filamentary structures [1][2][3][4] are a fundamental feature of magnetized plasmas that are far from thermal equilibrium. Magnetic field-aligned filamentary structures can consist of density depletions or enhancements, localized pressure changes, current channels, charged flux tubes, or combinations thereof, depending upon the specific boundary conditions and sources that drive the plasma away from thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…A stream is considered narrow if its transverse dimension is on the order of the larger of the electron skin-depth (c/ pe , where c is the speed of light and pe is the electron plasma frequency) or the ion gyroradius. This situation may be encountered in magnetic reconnection studies [1], dynamo models [2,3], satellite and rocket observations of depleted flux tubes in the auroral ionosphere [4,5], structured small-scale Alfven waves, and laboratory studies of striation formation. The low frequency (below the ion cyclotron frequency, i Ω < ω ) parallel electric fields associated with these environments are capable of producing large parallel drifts, v D , in the electron distribution function that are unstable to high frequency electrostatic modes (in the LH range).…”
Section: Overviewmentioning
confidence: 99%
“…The broader interest in exploring the properties of drift waves in microscopic filaments is that, increasingly, it is being recognized [5][6][7][8][9][10][11] that filamentary structures are a fundamental feature of magnetized plasmas that are far from thermal equilibrium. Specifically, density depletions of the type investigated in this study have been observed in widely different environments including ionospheric heating experiments, 12 in situ measurements of the auroral iono-sphere by rockets 13 and spacecraft, 14 and in radar and rocket studies 15 of the equatorial F region.…”
Section: Introductionmentioning
confidence: 99%